Impact and resilience strategy of MSMEs in facing the COVID-19 pandemic: An empirical study on MSMEs in Indonesia - Hartomi Maulana; Kazi Md Tarique; Rahma Yudi Astuti; Soritua Ahmad Ramdani Harahap (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study aims to empirically examine the influence of COVID-19 on changes in the performance of MSME (micro, small and medium enterprises). The research also examines business resilience strategies in response to PPKM's orders amid the COVID-19 pandemic crisis in Indonesia. Quantitative and qualitative approaches were applied in this study. Primary data was collected through questionnaires, and interviews involving 477 respondents from MSME owners and six selected respondents in Indonesia employed in this study. Descriptive analysis and regression using structural equation modeling (SEM) were applied. The study showed that the dimensions of COVID-19, namely PPKM and health protocols, negatively affect MSME's performance. The study also found that promoting and selling products on social media, product diversification, and minimalizing cost production are among the most popular business resilience strategies to survive MSME's operation during the COVID-19 pandemic. The results suggest that the establishment of COVID-19's impact on MSME's performance should be aware and concerned. The study also indicates that MSMEs should be able to maintain their strategies in surviving their business due to the COVID-19 crisis.